2010
DOI: 10.1007/s12011-010-8882-z
|View full text |Cite
|
Sign up to set email alerts
|

The Redox Status in Rats Treated with Flaxseed Oil and Lead-Induced Hepatotoxicity

Abstract: Lead is a persistent environmental pollutant, and its toxicity continues to be a major health problem due to its interference with natural environment. In the present study, we have evaluated the effect of flaxseed oil on lead acetate-mediated hepatic oxidative stress and toxicity in rats. Lead acetate enhanced lipid peroxidation and nitric oxide production in both serum and liver with concomitant reduction in glutathione, catalase, superoxide dismutase, glutathione reductase, glutathione-S-transferase, and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 47 publications
9
33
0
Order By: Relevance
“…In addition, the hepatocytes lost their normal architecture and vacuolization with pyknotic nuclei appeared in the cytoplasm. These results are in agreement with the results of Abdel-Moneim et al [46]. Our histological investigations of renal tissue revealed that Pb-acetate treatment results in progressive glomerular and tubular alterations.…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the hepatocytes lost their normal architecture and vacuolization with pyknotic nuclei appeared in the cytoplasm. These results are in agreement with the results of Abdel-Moneim et al [46]. Our histological investigations of renal tissue revealed that Pb-acetate treatment results in progressive glomerular and tubular alterations.…”
Section: Discussionsupporting
confidence: 94%
“…These results are in accordance with those obtained previously for punica [36] and for silymarin [37].…”
Section: Effect On Oxidative Stress Biomarkerssupporting
confidence: 93%
“…Ibrahim et al (27) reported elevated plasma bilirubin levels in rats that were treated with lead acetate. Similarly, when examining rats exposed to lead through intraperitoneal injections, Abdel-Moneim et al (37) observed elevated serum bilirubin concentrations. Berrahal et al (34) observed significantly increased plasma bilirubin levels in rats that had been injected with 15 mg/kg of lead acetate.…”
Section: Discussionmentioning
confidence: 94%